Aquafeed formulation - Nates, Sergio F., 1961- (Oxford : Academic Press, an imprint of Elsevier, 2016)
Aquafeed Formulation is the only resource that provides summaries with examples and formulation techniques specifically to meet the needs of anyone in the aquaculture industry. As feed is the largest single cost item in aquaculture production, and formulating aquaculture feed requires many combinations of several ingredients and nutrient requirements, this book takes a clear-and -concise approach, providing essential information on formulation and covering relevant available software, feed nutrients, and additives such as enzymes and phytase and conjugated fatty acids, as well as best industry practices to improve aquafeed production. Users will find this to be a one-stop resource for anyone interested or involved in, the global aquaculture industry.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed October 14, 2015).
Keywords: Aquaculture; Feeds -- Composition; Feeds -- Analysis; Aquaculture industry; TECHNOLOGY & ENGINEERING / Agriculture / General; Aquaculture; Aquaculture industry; Feeds -- Analysis; Feeds -- Composition; Electronic books